Effectiveness Analysis of DNS Filtering on Cyberslacking Control - Firmansyah Pipii; Syahrial; Rizal Lamusu; Irawan Ibrahim (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
The development of information technology in educational environments has increased internet accessibility to support learning activities, but it has also contributed to cyberslacking behavior, namely the use of the internet for non-academic activities during study hours. This study aims to analyze the effectiveness of MikroTik-based DNS Filtering in controlling access to non-productive websites within educational networks. The research employed a quantitative approach with a quasi-experimental design by comparing network conditions before and after the implementation of DNS Filtering. Additional testing was conducted under Virtual Private Network (VPN) and DNS over HTTPS (DoH) scenarios to identify system limitations. Data analysis was performed using the Confusion Matrix method with evaluation parameters including accuracy, precision, recall, F1-score, and specificity. The results indicate that DNS Filtering effectively blocks access to non-productive websites under normal network conditions with a high level of accuracy without disrupting access to educational resources. The system was also able to classify productive and non-productive websites appropriately based on the implemented filtering rules. However, the effectiveness of the system decreased when users utilized VPN and DoH as bypass methods, indicating the limitations of conventional DNS-based filtering approaches. This study concludes that MikroTik-based DNS Filtering is a lightweight, easy-to-implement, and sufficiently effective solution for controlling cyberslacking in educational environments, although it still requires integration with additional network security methods to improve resistance against bypass techniques.